Interpolative Contraction and Discontinuity at Fixed Point on Partial Metric Spaces - Adhikari, Nabaraj (Nepal Journal of Mathematical Sciences, 2025)
This paper proposes a novel technique for solving Rhodes’ discontinuity problem by exploiting the features of a self-mapping that has a fixed point but is not continuous at that point within a partial metric space. Moreover, we investigate some geometric properties of FT under interpolative-type contractions and establish a few results related to fixed-discs and fixed-circles.